PROGRAM BIMBINGAN DAN KONSELING BAGI SISWA TUNANETRA DI SEKOLAH INKLUSIF - Mangkuwibawa, Hilman (Psympathic : Jurnal Ilmiah Psikologi, 2018)
One of the basic change in exceptional education is inclusive program. The most perspective population to have inclusive program are blind students. Potential development of blind students in inclusive program is not adequate with educational intervening class butÂ guidance and counseling. This research aims to formulate guidance and Counseling program for blind students who are studying at YPI Senior High School Bandung through inclusive program. The result of this research produce guidance and counseling program which consist of (1) information service guidance (2) academic guidance and (3) social personal guidance.